Fluorine removal from sodium tungstate ion exchange effluent by precipitation with addition of lanthanum chloride - Wan, Linsheng; Zhao, Lifu; Cao, Caifang; Gong, Dandan; Zeng, Xuepin; Yang, Liang (Frontiers in Chemistry, 2023)
The waste water generated from the sodium tungstate ion exchange process of scheelite hydrometallurgical extraction contains a certain concentration of fluorine ion, which caused environmental pollution and harmed human health. In this study, a new method for removing fluorine from the wastewater by precipitation with addition of lanthanum chloride was proposed. In the process, fluorine was removed by from the solution as insoluble lanthanum fluoride precipitates. To explore the favourable conditions for the formation of lanthanum fluoride, thermodynamic analysis of the La-F-H2O system was conducted. Results show that lanthanum fluoride is stable when the solution pH value is between 1.0 and 10.0, and the lanthanum fluoride is gradually converted into lanthana hydroxide when the pH value is more than 10.0 at 298K. The effects of various parameters on the fluorine removal were studied, and the optimum process parameters were determined. More than 92% of the fluorine can be removed when the concentration of fluorine in the solution ranged from 60 to 400 mg/L, the dosage of lanthanum chloride was 1.3 times of the theoretical amount, the pH value was 8.0 at 60°C for 30 min. After removing fluorine from the solution, the resiual fluorine concentrtion was lower than 10 mg/L, which could meet the requirement of national wastewater discharge.